Evaluation of molecular typing techniques to assign genetic diversity among Saccharomyces cerevisiae strains. - Baleiras Couto, M M (1996)
Discrimination of strains within the species Saccharomyces cerevisiae was demonstrated by the use of four different techniques to type 15 strains isolated from spoiled wine and beer. Random amplified polymorphic DNA with specific oligonucleotides and PCR fingerprinting with the microsatellite oligonucleotide primers (GAC)5 and (GTG)5 enabled discrimination between the strains tested. Additionally, restriction enzyme analysis, with TaqI and MseI, of PCR-amplified fragments from the complete internal transcribed spacer and nontranscribed spacer, both present in the rRNA-encoding gene cluster, proved to be suitable for generating intraspecies-specific patterns. Random amplified polymorphic DNA with primers 24 and OPA-11 and PCR fingerprinting with primer (GTG)5 appeared to generate the highest degree of diversity. However, the results indicated that there was no single PCR-mediated typing technique enabling discrimination on the strain level. Discrimination of each individual strain was nevertheless possible by combining the results obtained with all typing techniques.